An Exploratory Examination of The Threshold Concepts in Strategic Management (Journal of Applied Business and Economics, 2023)
Threshold concepts are core concepts in a field that students find particularly troublesome to understand, often because they integrate what students previously believed were discrete concepts or because they span boundaries between concepts or fields. Consequently, they are often transformative in nature and irreversible once fully understood. Therefore, they should form the core of our pedagogy.Threshold concepts have yet to be identified in strategic management. In this exploratory study, we examine student perceptions to determine which strategy concepts are likely threshold and identify four candidates: vertical integration, corporate diversification, innovation, and governance. In addition, we identify three non-core concepts - PESTEL, global strategies, and the balanced scorecard – that possess threshold-like characteristics, suggesting we rethink their curricular value.Finally, we identify active learning strategies that help students understand threshold concepts: applying/using the concept, discussing it with peers, and exploring examples. Class time devoted to such learning activities facilitates students “crossing the threshold.”
Keywords: business; economics; strategic management; strategy curriculum; threshold concept; threshold-like concept; core concepts; pedagogy